New 1:20,000 scale geological maps, synthesis and history of investigation of the Isua supracrustal belt and adjacent orthogneisses, southern West Greenland: A glimpse of Eoarchaean crust formation and orogeny - Nutman, Allen; Friend, Clark (Precambrian Research)
The Isua area in the Nuuk region, southern West Greenland contains the Eoarchaean Isua supracrustal belt (mostly amphibolites derived from basalts, with chemical sedimentary rocks, felsic rocks and ultramafic units) and orthogneisses with similar ages that flank it to the north and south. These rocks suffered polyphase metamorphism up to amphibolite facies conditions and strain is generally high, but nonetheless the Isua area has most of the world's occurrences of Eoarchaean rocks preserved in a low strain state. This means that structural, geochemical and isotopic studies of Isua area rocks can provide the least ambiguous data on the origin and tectonic evolution of Eoarchaean crust. New Isua colour digital geological maps at 1:20,000 scale (observed outcrop geology and interpretive solid geology) and a synthesis are presented here. These incorporate advances in structural observations, re-interpretations of the lithologies and the large amounts of zircon dating produced since publication in 1986 of the last geological map of the entire Isua area. Essential in the synthesis is that the Isua area contains a southern ca. 3800 Ma terrane and a northern ca. 3700 Ma terrane. Many of the rocks in the two terranes of different age are broadly similar in appearance, but have been distinguished by U-Pb zircon dating. The boundary between the terranes lies within the Isua supracrustal belt and is most likely at a highly tectonised unit of chert, BIF and carbonate rocks named the dividing sedimentary unit, that contains sparse 3940-3750 Ma detrital zircons. In the ca. 3700 Ma terrane to the north, no >3750 Ma detrital zircons have been found. The Isua supracrustal belt part of the ca. 3700 Ma northern terrane has three geochemically distinct sub-terranes dominated respectively by ≥3715 Ma boninites, ≥3715 Ma island arc tholeiites plus picrites and 3710-3700 Ma andesitic-dacitic rocks or sediments derived from them. In the Eoarchaean, these different arc- and maybe fore-arc related rocks were imbricated and juxtaposed ...